2016
DOI: 10.3144/expresspolymlett.2016.30
|View full text |Cite
|
Sign up to set email alerts
|

Segmented linear shape memory polyurethanes with thermoreversible Diels-Alder coupling: Effects of polycaprolactone molecular weight and diisocyanate type

Abstract: Abstract. Segmented linear polyurethanes (PUs) containing Diels-Alder (DA) adduct were synthesized in toluene solution from poly("-caprolactone) (PCL, M n = 10, 25 and 50 kg/mol), diisocyanate (methylene diphenyl diisocyanate (MDI), 2,4-toluene diisocyanate (TDI), 1,6-hexamethylenediisocyanate, (HDI)), furfurylamine (FA) and bismaleimide (BMI). The order of the segments in the PUs was -PCL-MDI-FA-BMI-. The PUs were characterized by size-exclusion chromatography (SEC), different spectroscopic ( 1 H-NMR, attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
(37 reference statements)
1
6
0
Order By: Relevance
“…According to Figure 4 and the data in Table 3 , the glass transition temperature ( T g ) of the samples containing PCD with M n = 2 kg/mol appears in the range from −50 to −40 °C, while T m values are around 20 °C (see Table 3 ). However, T m -s of higher molecular weight PCL segments (e.g., M n = 10 kg/mol) appear at around 60 °C, which is in good agreement with former works on PUs with PCL segments [ 30 , 31 ]. In the case of samples with increasing EP contents (see EP-PU 2 and 6), the Δ H m , and thus the crystallinity values, decreased considerably.…”
Section: Resultssupporting
confidence: 91%
“…According to Figure 4 and the data in Table 3 , the glass transition temperature ( T g ) of the samples containing PCD with M n = 2 kg/mol appears in the range from −50 to −40 °C, while T m values are around 20 °C (see Table 3 ). However, T m -s of higher molecular weight PCL segments (e.g., M n = 10 kg/mol) appear at around 60 °C, which is in good agreement with former works on PUs with PCL segments [ 30 , 31 ]. In the case of samples with increasing EP contents (see EP-PU 2 and 6), the Δ H m , and thus the crystallinity values, decreased considerably.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, T g,DSC increases with increase in the NCO/OH molar ratio. This fact might be due to the increase in the H‐bonding as well as the crosslinking density with the increase in the NCO/OH molar ratio . On Table , it can be observed that T g,DSC values of PTMG‐based SMPUs are higher than T g,DSC values of PEG‐based SMPUs.…”
Section: Resultsmentioning
confidence: 93%
“…Nowadays, a large number of works have reported the synthesis and characterization of SMPUs. For example, Lakatos synthesized various segmented linear SMPUs containing Diels‐Alder coupling in the main chain and studied their basic mechanical, shape memory and thermomechanical behavior. Moreover, Zhuo et al studied systematically the thermal properties of shape memory polyurethane nanofibrous nonwoven, from the morphology of nanofibers, crystalline structure, isothermal crystallization behavior, and thermal dependent strain recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Crosslinked polymers containing furfuryl and maleimide groups have been reported as well as linear alternatives but the synthetic routes are susceptible toward irreversible side‐reactions (particularly the Michael‐addition which occurs when maleimides are reacted in the presence of free nucleophiles at elevated temperature) or they involve the use maleimides that are not readily commercially available or the perspective is different from ours focusing on other applications including shape memory materials . An elegant approach is presented by Defize et al .…”
Section: Introductionmentioning
confidence: 99%